Assessment of neurologists' knowledge regarding intravenous fibrinolytic therapy for acute stroke in Shanxi province in China - Liansheng Ma; Xiaoyuan Niu; Wei Zhang; Yalan Fang; Jie Wang (BMC, 2017)
Abstract Background Limitations in physicians' knowledge regarding fibrinolytic therapy for acute ischemic stroke may contribute to low rate of fibrinolytic therapy in China. Here physicians' knowledge was surveyed on intravenous fibrinolytic therapy for acute ischemic stroke. Methods Neurologists (n = 175) from 27 major general hospitals in Shanxi province, P. R. China, were invited to complete questionnaires regarding their basic knowledge of intravenous fibrinolytic therapy for acute ischemic stroke. The questionnaire contained 12 multiple-choice questions. One point was assigned for a correct answer and zero point for a false or unanswered question. Results One hundred and thirty-one neurologists (74.9%) responded to the questionnaires. The mean accuracy rate of 12 questions was 54.9 ± 25.01% (range 0.8-96.2%). The mean total score for respondents was 6.59 ± 2.03 (range 2-11). More years of experience and higher academic degrees were independent factors related to the total scores (P = 0.000 and P = 0.004, respectively). Conclusions The neurologists in this study were knowledge deficient in the area of intravenous fibrinolytic therapy for acute ischemic stroke. This partially accounts for the low rate of fibrinolytic therapy in China.